Trends in pharmacological prescriptions and polypharmacy for personality disorders: a 10-year cross-sectional analysis of naturalistic data - Flavio Di Leone; Steinn Steingrimsson; Hanne Krage Carlsen; Sophie I. Liljedahl; Peter Sand (BMC Psychiatry)
Abstract Introduction The purpose of this study was to examine trends in prescribing practices for individuals diagnosed with personality disorders (PD) over a 10-year period in a major metropolitan area in Sweden. Our aim was to assess the alignment of prescribing patterns with national clinical guidelines. Methods A register analysis was conducted on 26,520 pharmacological prescriptions from patients' Electronic Health Records (EHRs), documented between January 2011 and December 2020. The study compared the annual proportion of prescriptions across various psychotropic medication classes over time between individuals diagnosed with PD alone and those diagnosed with PD and co-occurring clinical conditions. Additionally, polypharmacy (≥ 3 psychiatric medications) was investigated in both groups. Results The proportion of individuals diagnosed with PD alone who received medication increased significantly over the study period. No significant changes were observed in polypharmacy, which remained prevalent in both groups. In the PD alone group, significant negative trends were observed in prescriptions for antidepressants, mood stabilizers, and benzodiazepine derivatives, while stimulant prescriptions rose significantly. In contrast, non-benzodiazepine sedatives and antipsychotics increased significantly in the group with co-occurring conditions. Conclusion Our study indicates mixed adherence to Swedish national prescribing guidelines for PD. While there was alignment with recommendations, such as reduced benzodiazepine use, challenges remain in addressing polypharmacy and the prescribing of medications without clear indications, particularly in individuals without comorbidities. These findings emphasize the need for improved diagnostic accuracy, ongoing clinician education, and the integration of prescribing data with diagnostic and treatment records. Future research should explore prescribing practices across various clinical settings and assess the influence of psychopharmacological trends on prescribing, while also defining polypharmacy in the context of personality disorders to guide clinical practice.